2016
DOI: 10.1111/1744-7917.12326
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome ofAnopheles minimus(Diptera: Culicidae) and the phylogenetics of knownAnophelesmitogenomes

Abstract: Anopheles minimus is an important vector of human malaria in southern China and Southeast Asia. The phylogenetics of mosquitoes has not been well resolved, and the mitochondrial genome (mtgenome) has proven to be an important marker in the study of evolutionary biology. In this study, the complete mtgenome of An. minimus was sequenced for the first time. It is 15 395 bp long and encodes 37 genes, including 13 protein-coding genes (PCGs), 22 transfer RNAs (tRNAs), two ribosomal RNAs (rRNAs) and a non-coding reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 48 publications
(67 reference statements)
4
16
0
Order By: Relevance
“…All 22 tRNA genes were dispersed in the mitochondrial genome of An. sinensis , the length and position of them was similar with the reported Culicidae mosquitoes (Table 2 ) [ 13 15 , 20 , 21 , 28 , 29 , 31 33 ]. Among them, there were two kinds of transfer genes for serine and leucine, and the remaining 18 tRNA genes correspond to the other amino acid respectively.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…All 22 tRNA genes were dispersed in the mitochondrial genome of An. sinensis , the length and position of them was similar with the reported Culicidae mosquitoes (Table 2 ) [ 13 15 , 20 , 21 , 28 , 29 , 31 33 ]. Among them, there were two kinds of transfer genes for serine and leucine, and the remaining 18 tRNA genes correspond to the other amino acid respectively.…”
Section: Resultssupporting
confidence: 83%
“…sinensis species consisted of 13 intron-less protein coding genes. The gene number, order and transcription direction of mitochondrial genes were the same as in other species of Culicidae species [ 13 15 , 17 , 19 , 21 , 28 33 ]. There were 9 genes located in the J strand, as ND2, CO1, CO2, ATPase8, ATPase6, CO3, ND3, ND6 and CytB, while ND1, ND5, ND4 and ND4L located in the N strand.…”
Section: Resultsmentioning
confidence: 99%
“…albopictus (Chen et al ., ) have been sequenced and annotated, and more recently 16 Anopheles genomes have been reported (Neafsey et al ., ). A number of transcriptomes and mitochondrial genomes have also been sequenced and comparatively analyzed (e.g., Chen et al ., ; Hua et al ., ; Hao et al ., ; Fang et al ., )…”
Section: Introductionmentioning
confidence: 99%
“…albopictus (Chen et al, 2015) have been sequenced and annotated, and more recently 16 Anopheles genomes have been reported (Neafsey et al, 2015). A number of transcriptomes and mitochondrial genomes have also been sequenced and comparatively analyzed (e.g., Chen et al, 2014;Hua et al, 2016;Hao et al, 2017;Fang et al, 2018) With the increasing of mosquito omics data, the diversity, characterization and functional analyses of a given group of genes are progressively increasing (He et al, 2016;Liu et al, 2018;Mei et al, 2018;Wang et al, 2018;Wu et al, 2018;Yan et al, 2018). However, the in silico SSR identification and analysis are relatively insufficient, and therefore the SSR features and the association with different species of mosquito genomes are still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial genome (mtgenome) information can provide unique evolutionary insights. Hua et al sequenced the complete mtgenome of Anopheles minimus and constructed a phylogenetic tree that included 18 other Anopheles species (Hua et al, 2016). Their results showed that the subgenera, Cellia and Anopheles, and Nyssorhynchus and Kerteszia, have mutually close relationships, respectively.…”
mentioning
confidence: 99%